Putative diazepam binding inhibitor peptide: cDNA clones from rat. - Mocchetti, I (1986)
cDNA clones corresponding to the polypeptide that has been shown to be an endogenous diazepam binding inhibitor and may act as a physiological ligand for the benzodiazepine/beta-carboline receptor have been isolated from bacteriophage lambda recombinant libraries from rat hypothalamus, total brain, and liver. The clones contain an open reading frame corresponding to 87 amino acids. A signal sequence is not present. In addition to high levels of mRNA in various brain regions, RNA blot analysis reveals an abundance of diazepam binding inhibitor mRNA in many peripheral organs (e.g., testes, kidney, liver, and heart) that are known to be rich in peripheral benzodiazepine recognition sites. The size of the mRNA in all tissue examined is approximately 0.7 kilobase. Southern blot analysis of genomic DNA suggests the presence of about six genes in the rat, some of which may be pseudogenes.